Two-dimensional metal–organic frameworks and their derivatives for electrochemical energy storage and electrocatalysis. Issue 2 (4th February 2020) - Zhao, Kuangmin; Zhu, Weiwei; Liu, Suqin; Wei, Xianli; Ye, Guanying; Su, Yuke; He, Zhen
Abstract : The recent progress on the fabrication of two-dimensional metal–organic frameworks and their derivatives as well as their applications in electrochemical energy storage and electrocatalysis are reviewed. Abstract : Two-dimensional (2D) metal–organic frameworks (MOFs) and their derivatives with excellent dimension-related properties, e.g. high surface areas, abundantly accessible metal nodes, and tailorable structures, have attracted intensive attention as energy storage materials and electrocatalysts. A major challenge on the road toward the commercialization of 2D MOFs and their derivatives is to achieve the facile and controllable synthesis of 2D MOFs with high quality and at low cost. Significant developments have been made in the synthesis and applications of 2D MOFs and their derivatives in recent years. In this review, we first discuss the state-of-the-art synthetic strategies (including both top-down and bottom-up approaches) for 2D MOFs. Subsequently, we review the most recent application progress of 2D MOFs and their derivatives in the fields of electrochemical energy storage ( e.g., batteries and supercapacitors) and electrocatalysis (of classical reactions such as the HER, OER, ORR, and CO2 RR). Finally, the challenges and promising strategies for the synthesis and applications of 2D MOFs and their derivatives are addressed for future development.